Evaluation of maternal rhesus blood type as a risk factor in adverse pregnancy outcomes in Korea: a nationwide health insurance database study - Yihua Jin; Meari Dong; Seung Woo Yang; Kyu-Min Lee; Sung Won Han; Shin Hee Seo; Ajin Lee; In Sook Sohn; Han Sung Kwon; Geum Joon Cho; Han Sung Hwang (Korean Society of Obstetrics and Gynecology, 2020)
Objectives The current study aimed to investigate whether pregnancy outcomes are affected by maternal rhesus (Rh) status by comparing the primigravida pregnancy outcomes of Rh-negative women with those of Rh-positive women. Methods The study data were collected from the Korea National Health Insurance Claims Database and the National Health Screening Program for Infants and Children. In total, 1,664,882 primigravida women who gave birth between January 1, 2007 and December 31, 2014, were enrolled in this study. As the risk and severity of sensitization response increases with each subsequent pregnancy, only primigravida women were enrolled. The patients were divided into 2 groups according to Rh status, and the pregnancy outcomes were compared. Results In total, 1,661,320 women in the Rh-positive group and 3,290 in the Rh-negative group were assessed. With regard to adverse pregnancy outcomes, there was no statistically significant difference between the 2 groups in terms of the prevalence of preeclampsia, postpartum hemorrhage, abruptio placenta, placenta previa, and uterine artery embolization. A univariate analysis revealed that none of the adverse pregnancy outcomes were significantly correlated to Rh status (preeclampsia: odds ratio [OR], 1.00, 95% confidence interval [CI], 0.81-1.23; postpartum hemorrhage: OR, 1.10, 95% CI, 0.98-1.24; abruptio placenta: OR, 0.80, 95% CI, 0.46-1.37; and placenta previa: OR, 1.08, 95% CI, 0.78-1.42). The adjusted ORs of postpartum hemorrhage and preterm birth did not significantly differ. Conclusion Maternal Rh status is not associated with adverse outcomes in primigravida women.